Stability of liquid films down an inclined plane - Phuong, Phan Thi Thu; Tran, Tran Van (Vietnam Journal of Mechanics, 2006)
In this paper, the problem of linear stability of viscous liquid films down an inclined plane is solved by finite difference method. It is applicable for moderate values of Reynolds and wave numbers. The obtained results by this method is compared with ones of some papers and with experimental data